On gas turbine conceptual design. - Kyprianidis, Konstantinos G. (Cranfield University, 2019)
The thesis begins with a review of the evolution of the industry's vision for the aero-engine design of the future. Appropriate research questions are set that can influence how this vision may further evolve in the years to come. Design constraints, material technology, customer requirements, noise and emissions legislation, technology risk and economic considerations and their effect on optimal concept selection are discussed in detail. Different aspects of the pedagogy of gas turbine conceptual design as well as information on the Swedish and Brazilian educational systems are also presented. A multi-disciplinary aero-engine conceptual design tool is utilised for assessing engine/aircraft environmental performance. The tool considers a variety of disciplines that span conceptual design including: engine performance, engine aero-dynamic and mechanical design, aircraft design and performance, emissions prediction and environmental impact, engine and airframe noise, and production, maintenance and direct operating costs. With respect to addressing the research questions set, several novel engine cycles and technologies - currently under research - are identified. It is shown that there is great potential to reduce fuel consumption for the different concepts identified, and consequently decrease the CO₂ emissions. Furthermore, this can be achieved with sufficient margin from the NOᵪ certification limits set by International Civil Aviation Organisation, and in line with the medium-term and long-term goals set through it's Committee on Aviation Environmental Protection. The option of an intercooled-core geared-fan aero-engine for long-haul applications is assessed by means of a detailed design space exploration. An attempt is made to identify the fuel burn optimal values for a set of engine design parameters by varying them all simultaneously, as well as in isolation. Different fuel optimal designs are developed based on different sets of assumptions. Evidence is provided that higher overall pressure ratio intercooled engine cycles become more attractive in aircraft applications that require larger engine sizes. The trade-off between the ever-increasing energy efficiency of modern aero-engines and their NOᵪ performance is assessed. Improving engine thermal efficiency has a detrimental effect on NOᵪemissions for traditional combustors, both at high altitude and particularly at sea-level conditions. Lean-combustion technology does not demonstrate such behaviour and can therefore help decouple NOᵪ emissions performance from engine thermal efficiency. If we are to reduce the contribution of aviation to global warming, however, future certification legislation may need to become more stringent and comprehensive, i.e., cover high altitude conditions. By doing so we can help unlock the competitive advantage of lean burn technology in relation to cruise NOᵪ and mission performance. Finally, some insight is provided on the potential benefits to be tapped from a transition from the traditional deterministic approach for system analysis to a stochastic (robust design) approach for economic decision-making under uncertainty. A basic methodology is outlined and applied on a specific conceptual design case for a conventional turbofan engine. The sensitivity of an optimal engine design obtained deterministically to real-life uncertainties is found to be far from negligible. The considerable impact of production scatter, measurement uncertainties as well as component performance deterioration, on engine performance must be catered for; this includes taking into consideration control system design aspects. A fast analytical approach is shown to be sufficiently accurate for the conceptual design process, particularly for estimating key performance parameters. These relate to type-test certification and performance retention guarantees including preliminary estimates of engine production margins. Lessons learned are presented from: (i) the integration of different elements of conceptual design in a new BSc course and an existing traditional MSc course on gas turbine technology, (ii) the development of an intensive course on gas turbine multi-disciplinary conceptual design. The results from the use of problem-based learning are very encouraging, in terms of enhancing student learning and developing engineering skills.
Keywords: Design constraints; material technology; customer requirements; noise; emissions; legislation; technology risk; economic considerations; engine performance; engine aerodynamic; mechanical design; aircraft design; environmental impact; operating costs